Quantifying demand-side management in sustainable grid networks by industrial load flexibility with variable inertia flywheel induction motors - Salam, Syed Munimus; Mohammad, Nur; Rashid, Muhammad Mahbubur (ScienceDirect, 2024)
The load flexibility of industrial induction motor is explored considering energy reduction strategies.T he usage of a spinning flywheel with an adjustable moment of inertia is suggested in this paper to increase energy efficiency. A variable inertia flywheel (VIF) is presented in this work to regulate rotational speed and lower power consumption. A few articles recently have examined how the flywheel affects electric motor performance and energy usage.T he creation of a prototype is used to assess the efficacy of the proposed VIF.T o verify the system's efficacy, experiments are conducted. A 33-bus sustainable grid is taken into consideration to assess the overall reduction in power usage in an industrial context. The analytical study aims to evaluate the impact of using industrial induction motors with VIF as demand side management (DSM) on total power consumption. The examination of power reduction and grid optimization across a sustainableI EEE 33 bus grid network is the main topic of the research. The results show how VIF may be used to lower overall energy usage for demand-side control in a sustainable grid